Climate Change Patterns in Two Districts of Odisha: A Trend Analysis - Damodar Jena, Nibal Dibiat (International Journal of Advanced Science and Technology, 2020)
Climate change has become a global phenomenon and a threat to not only human being, rather to all living being. It demands a well planned and systematic response from all sectors at global and local levels. The expected adverse effects of climate change on both the humans and the environment makes it the matter of concern for the economy especially for the agricultural sector. The three important parameters of climate change, e.g. rainfall, temperature and relative humidity determine the fate of agricultural outputs and its whole processes. The present paper analyses the climate change patterns by using the Mann-Kendal Test and Sen’s Slop. An increase in temperature and decline in rainfall trends may result in more droughts in coming years, which need to be effectively adapted by the farmers with relevant policy provisions and farmer friendly program interventions especially in the month of June.